MENELUSURI NILAI-NILAI RELIGIUSITAS NOVEL “HAFALAN SHALAT DELISA” KARYA TERE LIYE - Hani Greisilavia Andaresta; Dimas Oky Kurnianto; Pardiyatmoko (Jurnal Bastra (Bahasa dan Sastra), 2025)
Literature, as an artistic medium, goes beyond narrative and plays a role in creative expression. The novel, a manifestation of prose, serves as a narrative vehicle that reveals the intricacies of life and the characters involved in it from beginning to end. There is a deep connection between literature and religiosity. One of the novels that has a rich religious theme and values is "Hafalan Shalat Delisa" by Tere Liye. This research aims to identify the religiosity values in the novel "Hafalan Shalat Delisa" by Tere Liye. This research is descriptive qualitative with data sources from the novel "Hafalan Shalat Delisa" and studied with the dialectical technique analysis method. The result of this research is the confirmation of four religious aspects in the novel "Hafalan Shalat Delisa", namely human relations with God, individual bonds with other individuals, human harmony with themselves, and human relations with nature.